1985
DOI: 10.2307/3586278
|View full text |Cite
|
Sign up to set email alerts
|

Learning Strategy Applications with Students of English as a Second Language

Abstract: Recent research on cognition has indicated the importance of learning strategies in gaining command over second language skills. Despite these recent advancements, important research questions related to learning strategies remain to be answered. These questions concern 1) the range and frequency of learning strategy uses by students learning English as a second language (ESL) and 2) the effects of training in learning strategies on English language skills. This study, which was conducted with high school ESL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
176
4
10

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(195 citation statements)
references
References 20 publications
5
176
4
10
Order By: Relevance
“…Cognitive strategies refer to manipulating or transforming the learning materials directly in specific learning tasks, such as repetition, translation, grouping, note-taking, deduction, recombination, imagery, auditory representation, keyword, contextualization, elaboration, transfer, and inferencing (O'Malley & Chamot, 1985). Metacognitive strategies refer to an overall control over the learning process, such as advanced organizers, direct attention, selective attention, self-management, planning, reasoning, monitoring, and self-evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive strategies refer to manipulating or transforming the learning materials directly in specific learning tasks, such as repetition, translation, grouping, note-taking, deduction, recombination, imagery, auditory representation, keyword, contextualization, elaboration, transfer, and inferencing (O'Malley & Chamot, 1985). Metacognitive strategies refer to an overall control over the learning process, such as advanced organizers, direct attention, selective attention, self-management, planning, reasoning, monitoring, and self-evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…There are three categories of strategies used by learners: cognitive, metacognitive and affective-social strategies (Brown & Palinscar, 1982;O'Malley & Chamot, 1985). Cognitive strategies refer to manipulating or transforming the learning materials directly in specific learning tasks, such as repetition, translation, grouping, note-taking, deduction, recombination, imagery, auditory representation, keyword, contextualization, elaboration, transfer, and inferencing (O'Malley & Chamot, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The questions are divided into three groups based on the classification of the metacognitive strategies: Planning for learning (1)(2)(3)(4)(5), Monitoring of one's production or comprehension (6---10), Evaluating of learning after an activity is completed (11---15).…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…For example, O'Malley et al (1985) carried out classroom observation from the perspectives of source, activity, setting, materials and approach concerning learning strategy, and interviews for both teachers and students to elicit strategies for specific learning tasks, the findings of which informed the training practice and were the basis of refining the training approaches. There are good considerations behind these attempts: firstly, it is now generally recognized that learner strategy use is very unlikely to be discussed thoroughly without taking into consideration the learner differences either individually or in groups (Macaro, 2006) such as age, gender, major and learning experience; Secondly, apart from the variables, the method used in this paper to elicit strategies is not without flaws.…”
Section: Learner Trainingmentioning
confidence: 99%
“…Abundant studies have demonstrated the great effect exerted by metacognitive strategies both in reading (Baker & Brown, 1984;Carrel et al, 1989;Talbot, 1995) and listening (O' Malley & Chamot, 1985;Schwartz, 1992;Yang, 2004). However, there is little research available to scrutinize the relationship between metacognitive strategies and vocabulary learning though conspicuously, vocabulary is central to language learning.…”
Section: Introductionmentioning
confidence: 99%